Clinical, Imaging, and Laboratory Characteristics of Adult Mexican Patients with Tuberculous Meningitis: A Retrospective Cohort Study - Miguel García-Grimshaw; Francisco Alejandro Gutiérrez-Manjarrez; Samuel Navarro-Álvarez; Alejandra González-Duarte (Journal of Epidemiology and Global Health, 2019)
Tuberculous Meningitis (TBM) is the most common form of central nervous system Tuberculosis (TB), accounting for 5–6% of extrapulmonary TB cases. Nowadays, TBM continues to be a major topic in public health because of its high prevalence worldwide. This retrospective study aimed to describe the clinical, laboratory, and imaging characteristics at admission; and in-hospital outcome of adult Mexican patients with TBM. We collected data from medical records of patients aged ≥18 years diagnosed with TBM according to the uniform case definition for clinical research who were treated at Tijuana General Hospital between January 2015 and March 2018 and compared them according to the subtype of diagnosis. We included 41 cases (26 males, median age 28 years, range 18–57 years), 13 (31.7%) patients were HIV positive, and 21 (51.2%) were illicit drug users. At admission, 7 (17.1%) patients were in stage I, 22 (53.6%) in stage II, and 12 (29.3%) in stage III. A definitive diagnosis was established in 23 (56.1%) patients, probable in 14 (34.1%), and possible in four (9.8%). Molecular testing was positive in 83% of the cases, yielding significantly higher positive results than other microbiological studies. There were eight (19.5%) deaths, without statistical difference between mortality and not having a definitive diagnosis (p = 0.109). We found that the baseline characteristics of our population were similar to those described by other authors worldwide. In this series, molecular testing showed to be very useful when used in the early stages, particularly in subjects with subacute onset of headache, fever, weight loss, and altered mental status.